2013
DOI: 10.4102/pythagoras.v34i2.232
|View full text |Cite
|
Sign up to set email alerts
|

Technological pedagogical content knowledge in South African mathematics classrooms: A secondary analysis of SITES 2006 data

Abstract: This article reports on a secondary data analysis conducted on the South African mathematics teachers’ dataset of the Second Information Technology in Education Study (SITES 2006). The sample consisted of a stratified sample of 640 mathematics teachers from 504 randomly selected computer-using and non–computer-using schools that completed the SITES 2006 teachers’ questionnaire, which investigated their pedagogical use of Information Communication Technology (ICT). The purpose of the current investigation was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Structured CPD to support mathematics teachers' TPACK has been linked with the successful integration of ICTs in schools (Lundall & Howell, 2000) and has a significant impact on learner achievement (Anthony & Walshaw, 2009). The effective use of ICTs in the mathematics classroom enhances learner productivity by saving time on calculations, reinforcing the relationship between curriculum and reality, scaffolding learners' exploration and experimentation, and providing immediate feedback (Leendertz et al, 2013). Leendertz et al (2013) found that if mathematics teachers master TPACK, their teaching of the subject is more effective.…”
Section: Barriers Affecting the Continuous Professional Development Of Mathematics Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Structured CPD to support mathematics teachers' TPACK has been linked with the successful integration of ICTs in schools (Lundall & Howell, 2000) and has a significant impact on learner achievement (Anthony & Walshaw, 2009). The effective use of ICTs in the mathematics classroom enhances learner productivity by saving time on calculations, reinforcing the relationship between curriculum and reality, scaffolding learners' exploration and experimentation, and providing immediate feedback (Leendertz et al, 2013). Leendertz et al (2013) found that if mathematics teachers master TPACK, their teaching of the subject is more effective.…”
Section: Barriers Affecting the Continuous Professional Development Of Mathematics Teachersmentioning
confidence: 99%
“…The results showed that although South African teachers indicated they were enthusiastic to learn new ways to make teaching and learning interesting, they encountered four barriers that hindered their pedagogical use of ICTs, namely confidence, time, access to resources, and professional development. In addition, Leendertz, Blignaut, Nieuwoudt, Els, and Ellis (2013) found that mastery of TPACK by mathematics teachers contributed to more effective mathematics teaching in South African schools. However, these studies did not relate mathematics teachers' current levels of TPACK and their barriers to integrating ICT to CPD programmes.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Technological pedagogical knowledge (TPK) refers to the affordances and constraints of technology as an enabler of different teaching approaches (Mishra & Koehler, 2006). Leendertz et al (2013) suggest that technology should be connected to pedagogy to add value to teaching and learning and therefore cannot be regarded as context-free. (7) TPACK refers to the knowledge and understanding of the interplay between CK, PK and TK when using technology for teaching and learning (Schmidt et al, 2009).…”
Section: Positsmentioning
confidence: 99%
“…Education in South Africa is altering invariably according to the stipulations by the Department of Education, such as the development of learning outcomes for the twenty-first century which recognize learners to use information in particular contexts (Department of Education [DOE], 2001;Law & Chow, 2008bin Leendertz, Blignaut, Nieuwoudt, Els, & Ellis, 2013. According to Maaga (2009, p. 1), the early childhood phase of birth to nine years of age is the most crucial phase for every person.…”
Section: Introductionmentioning
confidence: 99%
“…The current study thus differs from these studies in that the focus is on pre-service teachers' practical application during teaching practice. Moreover, the use of TPACK instruments in South Africa is still in its infancy as it has only been successfully used in a secondary data analysis study investigating the level of TPACK for grade 8 mathematics in-service teachers (Leendertz et al, 2013). Most of the international studies that trace the development of TPACK for specific subjects indicate high levels of development of the TPACK knowledge dimensions.…”
Section: Review Of Relevant Literature and Theoretical Frameworkmentioning
confidence: 99%